A Strategy for the Production of Single-Cell Proteins by the Efficient and Continuous Fermentation of Hydroxide Bacteria Under Gas Fermentation - Shuai Fu; Longyu Gou; Ke Long; Lanchai Chen; Dingrong Cai; Yue Lu (Applied Sciences)
Cupriavidus necator can produce single-cell proteins (SCPs) using electrons produced by hydrogen as energy, oxygen as electron acceptors, and CO2 as carbon sources. Gas fermentation is a process of microbial fermentation that uses gas substrates (such as hydrogen, carbon dioxide, etc.) which faces several challenges, mainly including the low solubility of gas substrates, the danger of hydrogen and oxygen mixing, and the optimization of fermentation conditions. To overcome these challenges, this article explores a variety of strategies—including the design of a self-developed bioreactor—to reduce the risk of static electricity. Without the addition of filler material, the results showed that the maximum cell dry weight (CDW) of 30% secondary seed inoculation was 20.41% higher than that of 10% secondary seed inoculum, and 5.99% higher than that of 20% secondary seed inoculum. Combined with the filler material and with the use of high-efficiency continuous fermentation technology, the average yield of continuous fermentation was 23.31 g/day, while the average yield of batch fermentation was 14.33 g/day. The daily yield of continuous fermentation is 1.63 times that of batch fermentation. These efforts are aimed at improving the efficiency and safety of gas fermentation.